IBADAH RUMAH TANGGA: KELUARGA SEBAGAI KUNCI PEMULIHAN GENERASI KECANDUAN GADGET DI GKSI EL-SHADDAI - Marbun, Tresa (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2024)
The growth of digital technology has changed many aspects of life, including the way children and young people connect and learn. The excessive use of gadgets among the younger generation has raised concerns about the negative effects on their physical, mental and spiritual health. In GKSI El-Shaddai Bojo, gadget addiction among children has started to affect their family life and their position in worship activities. This post aims to examine the position of household worship as a recovery facility for the gadget-addicted generation. This research was attempted using participatory observation and training procedures carried out at GKSI El-Shaddai Bojo, West Sulawesi. The results of this PkM activity show that household worship can be an efficient medium in reducing gadget dependence and strengthening spiritual values in the family. Through togetherness in prayer, praise, and dialogue of God's Word, the family is expected to produce an area conducive to the spiritual growth of children, while building their personalities to be able to experience the challenges of the digital age.